2013
DOI: 10.1590/s0104-11692013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Current status of Complementary Therapies in Spain in nursing degree

Abstract: Complementary Therapies training in Spain is deficient because it is not collected as a core subject and / or obligatory. The absence of Complementary Therapies in the curriculum, questions such as their value in training, conceptualization which teachers, the impact on quality of care, training of teachers responsible for teaching the subject, as well as the number of credits and the course being in the degree of Grado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…The results show that the Education students, along with the Nursing students, are those who presented the highest level of agreement concerning these therapies compared with the Medicine and Journalism students, who agreed the least. As concerns nursing, Fernández-Cervilla et al (2013), considered complementary therapies' absence from nursing curriculums to be a mistake due to the positive repercussions that this training could have on the quality of patient care. Thus, this study corroborates that, as shown in…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the Education students, along with the Nursing students, are those who presented the highest level of agreement concerning these therapies compared with the Medicine and Journalism students, who agreed the least. As concerns nursing, Fernández-Cervilla et al (2013), considered complementary therapies' absence from nursing curriculums to be a mistake due to the positive repercussions that this training could have on the quality of patient care. Thus, this study corroborates that, as shown in…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the Education students, along with the Nursing students, are those who presented the highest level of agreement concerning these therapies compared with the Medicine and Journalism students, who agreed the least. As concerns nursing, Fernández-Cervilla et al (2013), considered complementary therapies' absence from nursing curriculums to be a mistake due to the positive repercussions that this training could have on the quality of patient care. Thus, this study corroborates that, as shown in Table 4, Education and Nursing are in alignment (favourable attitude towards complementary therapies), as are Medicine and Journalism (unfavourable attitude towards complementary therapies).…”
Section: Resultsmentioning
confidence: 99%
“…Among the various techniques of therapy, massage therapy and music therapy were mentioned in the selected studies (17)(18) . Nowadays, there has been a growing demand for complementary therapies in order to overcome the biomedical-technical model, so that the patient can feel relaxed, supported, experience well--being, internal strength and cope with the disease (21) .…”
Section: Discussionmentioning
confidence: 99%